2014
DOI: 10.1007/s00005-014-0286-x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clocks and Inflammation: Reciprocal Regulation and Shared Mediators

Abstract: The immune system is deeply interconnected with the endogenous 24-h oscillators of the circadian system. Indeed, the connection between these two physiological systems occurs at multiple levels and in both directions. On one hand, various aspects of the immune system show daily rhythms, which appear to be essential for healthy immune maintenance and proper immune response. On the other hand, immune responses cause changes in circadian rhythms, disrupting their delicate balance and manifesting in disease. Indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 183 publications
1
51
0
1
Order By: Relevance
“…These direct effects on the central nervous system and HPA axis circuits, including the amygdala, hippocampus and peripheral tissue glucocorticoid receptors, can be related with altered basal HPA axis activity. Stress reactivity patterns can also influence basal HPA axis activity indirectly through the multi-directional influence between HPA axis, immune system and circadian clock rhythm (Cermakian et al, 2014; Nader et al, 2010; Scheiermann et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…These direct effects on the central nervous system and HPA axis circuits, including the amygdala, hippocampus and peripheral tissue glucocorticoid receptors, can be related with altered basal HPA axis activity. Stress reactivity patterns can also influence basal HPA axis activity indirectly through the multi-directional influence between HPA axis, immune system and circadian clock rhythm (Cermakian et al, 2014; Nader et al, 2010; Scheiermann et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, mounting evidence has demonstrated that the immune system displays circadian oscillations (see reviews (Labrecque and Cermakian 2015;Nakao 2014;Scheiermann et al 2013;Cermakian et al 2013;Cermakian et al 2014)). Pro-inflammatory cytokines are elevated during rest time and anti-inflammatory cytokines are elevated during activity time.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that disruption of the circadian clock leads to dysregulation of immune responses which underlie the pathophysiological basis of disease, suggesting an important regulatory role of the circadian system. This relates to daily oscillations in the number of circulating innate and adaptive immune cells, cytokine and chemokine levels and expression of adhesion molecules that are integral components of the immune response (reviewed in (Labrecque and Cermakian 2015;Nakao 2014;Scheiermann et al 2013;Cermakian et al 2013;Cermakian et al 2014)). Overall, multiple studies suggest that pro-inflammatory activity is elevated during rest and induces sleep whereas anti-inflammatory mediators are induced upon awakening and inhibit sleep (Bryant et al 2004;Krueger 1990;Krueger et al 2001;Kushikata et al 1999;Krueger 1987;Kubota et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…33 Circadian rhythms have a direct impact on the systemic regulation of energy metabolism and immune, 34 hormonal, 30 and cardiovascular functions. 35 Their chronic disruption increases susceptibility to inflammatory and metabolic disorders, 34,36 indicating a protective role for circadian rhythms against incidence of disease.…”
Section: Ra and Circadian Rhythmsmentioning
confidence: 99%